Segmentation for pulmonary artery from mediastinum to lung in CTA datasets. (1st January 2013) - Zhang, Jiehui; He, Zhongshi; Dehmeshki, Jamshid
This paper presents a novel approach for segmenting and tracking pulmonary artery tree from mediastinum to lung in computed tomography angiography images. An algorithm based on region growing and slice marching methods is proposed for vessel tree tracking, and the approach also combines with context-contour-based mediastinum segmentation, feature map filter, and 3D morphological techniques to assist the track of pulmonary artery in avoiding leakage problem. We have evaluated our method on 18 continuous clinical patient data and demonstrated its ability to correctly separate pulmonary arteries from other blood vessels, and robustly handle noise.